Level control experiment via Internet - Salleh Hanim; Yusaf Talal F.; Azlan M.Khafif Zol (2023)
This project is a result of a number of tests and experimental work that been carried out at the UNITEN laboratory to control the water level via Internet (using LabVIEWTM). The experimental setup consists of water tank, sump, level sensor, proportional valve and centrifugal pump. The computer data acquisition and control system use plug-in module which consist of a converter, a digital input/output module, an analog output module and an analog input module. This project also represents the first phase of controlling and operating stationary single cylinder four stroke diesel engine.